Papillary Intralymphatic Angioendothelioma in a Child With PIK3CA-Related Overgrowth Spectrum: Implication of PI3K Pathway in the Vascular Tumorigenesis. (March 2023) - Debelenko, Larisa; Mansukhani, Mahesh M.; Remotti, Fabrizio
Papillary intralymphatic angioendothelioma (PILA) is an extremely rare vascular tumor and its pathogenesis is unknown. Phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA)-related overgrowth spectrum (PROS) is a heterogeneous group of disorders caused by mosaicism for activating mutations of PIK3CA and characterized by asymmetric overgrowth, skeletal anomalies, skin lesions, and vascular malformations. An association between PILA and PROS has not been known. We report a case of PILA involving the spleen of a young girl with the clinical and molecular diagnosis of PROS. Sequencing of the patient's germ-line DNA detected a pathogenic PIK3CA variant c.1357G>A in 10.6% of alleles. Splenectomy revealed a 4-cm tumor composed of ectatic lymphatics with intraluminal papillary projections, consistent with PILA. The tumor cells showed immunohistochemical expression of CD31, CD34, ERG, FLI-1, PROX1, and caldesmon, while D2-40 was negative. The latter may suggest that the tumor derived from an endothelial precursor arrested in the final steps of lymphothelial differentiation, in keeping with the known role of the PIK3CA -governed molecular pathway in the progression of vascular progenitors to mature endothelial cells. The data implicates PIK3CA in the pathogenesis of PILA and broadens the spectrum of phenotypic expressions of PROS.